2015
DOI: 10.5267/j.ac.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Stock market liquidity and firm performance

Abstract: This paper investigates the relation between stock liquidity and firm performance. Liquidity plays an important role on performance of firms listed in Stock Exchange. When there is a good flow of trading stocks, people could expect more financing through absorbing investors on the market. This study examines the relationship between stock market liquidity and firm performance. The sample of the study was the continuously NSE listed top ten indices over the period [2005][2006][2007][2008][2009][2010][2011][2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
3
6
0
Order By: Relevance
“…Furthermore, empirical results reveal that the larger firms have high firm value. The findings of this paper are similar to the findings of Fang et al (2009); Wu and Liu (2009) and Singh et al (2015). Research findings shed light on the important role of stock market liquidity of the company in improving firm value.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, empirical results reveal that the larger firms have high firm value. The findings of this paper are similar to the findings of Fang et al (2009); Wu and Liu (2009) and Singh et al (2015). Research findings shed light on the important role of stock market liquidity of the company in improving firm value.…”
Section: Discussionsupporting
confidence: 89%
“…Amivest measure (LR), introduced by Copper, Groth, and Avera (1985), that compares daily returns with daily volume measured in number of shares is used (1) where, Vi, t = The trading volume for stock i on day t |Ri,t| = The absolute return for stock i on day t…”
Section: Liquidity (Independent Variable)mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of this, many researchers such as Singh et al (2015), Sidhu (2016), Singh (2017), and Pham et al (2020) have shown interest in the concept of performance, and efforts have been made to determine the factors that influence corporate performance to nip in a bud several issues pertaining to its undesired trend. Their findings revealed that the performance of companies has been deteriorating over the years due to many factors.…”
Section: Introductionmentioning
confidence: 99%
“…Several alternatives to conventional sintering of green compacts composed of nanosize particles have been proposed aiming at improving the mechanical and electrical properties associated with higher density and smaller average grain size [36]. In this context, microwave radiations are found to be advantageous as a result of the economy of energy and time during processing [37].…”
Section: Introductionmentioning
confidence: 99%